Pembelajaran Kimia secara Daring di SMA Negeri 5 Palangka Raya - Christina Nopriani (Jurnal Ilmiah Kanderang Tingang, 2023)
Since online learning was implemented, SMA Negeri 5 Palangka Raya as part of the education implementers in Central Kalimantan has been trying to find solutions and innovate to provide the best educational services for students. Likewise in learning chemistry, chemistry teachers must ensure that students can accept the concepts and material provided through online learning. This study aims to explore students' constraints and difficulties in conducting online learning related to understanding concepts in chemistry learning. This research also provides an overview of the implementation of online learning and evaluations that need to be carried out in preparation for the new school year. The subjects in this study were 103 students of class XI MIPA at SMA Negeri 5 Palangka Raya. Data was obtained from student responses regarding chemistry learning during the Covid-19 Pandemic using an online questionnaire. Then it is processed by changing each response to the question items into a percentage of the number of responses and triagulated with responses in the form of reasons. From the results of the study, it was concluded that most students can carry out online learning with various learning platforms. The level of attendance and enthusiasm of students is quite high and some students do not feel burdened by online learning. In terms of material understanding, difficulties are felt in material related to symbols, formulas, calculations and reaction mechanisms as well as microscopic aspects. Obstacles that are felt are divided into technical constraints, constraints on teaching methods and materials, as well as internal student constraints.